Alpha-amylase as the culprit in an occupational mealworm allergy case - Ganseman, Eva; Ieven, Toon; Frans, Glynis; Coorevits, Lieve; Pörtner, Noëmie; Martens, Erik; Bullens, Dominique MA; Schrijvers, Rik; Breynaert, Christine; Proost, Paul (Frontiers in Allergy, 2022)
Background: Occupational allergy has been described in employees working in contact with mealworms in pet stores, live fish bait or infested stored grains. More recently, mealworm farming became of interest for animal feed and human consumption, leading to occupational allergy cases in this industry too. Mealworm allergens linked to occupational allergy are troponin C, early-staged encapsulation inducing protein, cockroach-like allergen, tropomyosin, arginine kinase and larval cuticle proteins. Objective: We here report a case of occupational mealworm allergy and studied the culprit component. Methods: Diagnosis done by skin prick, specific IgE, basophil activation and lung function testing. Purification of allergens was done by anion-exchange chromatography and immunoblotting with patient IgE. Allergens were identified by in-gel trypsin digest and tandem mass spectrometry. Allergenicity and specificity further confirmed by IgE inhibition and passive basophil activation experiments. Results: We describe a new case of occupational mealworm allergy in a laboratory worker, with sensitization to different developmental stages and derivates of the mealworm, confirmed by skin prick and basophil activation tests. Despite strong sensitization to mites, the patient did not show cross-reactivity to other insects. We were able to identify alpha-amylase as the main allergen by immunoblotting, in-gel trypsin digestion and tandem mass spectrometry. Through inhibition experiments, we demonstrated that low amounts of this allergen could completely inhibit mealworm specific IgE. Moreover, passive BAT experiments demonstrated the IgE-alpha-amylase interaction to be functional, inducing degranulation in healthy donor basophils. Conclusion: Alpha-amylase can be identified as the responsible allergen in this specific case of occupational mealworm allergy.